Siderophore Biosynthesis but Not Reductive Iron Assimilation Is Essential for the Dimorphic Fungus Nomuraea rileyi Conidiation, Dimorphism Transition, Resistance to Oxidative Stress, Pigmented Microsclerotium Formation, and Virulence - Li, Yan; Wang, Zhongkang; Liu, Xuee; Song, Zhangyong; Li, Ren; Shao, Changwen; Yin, Youping (Frontiers in Microbiology, 2016)
Abstract: Iron is an indispensable factor for the dimorphic insect pathogenic Nomuraea rileyi to form persistent microsclerotia which can replace conidia or blastospores for commercial mass production. There are two high affinity iron acquisition pathways in N. rileyi, siderophore-assisted iron mobilization and reductive iron assimilation systems. Transcription of the two iron uptake pathways related genes is induced under iron-limiting conditions. Stage-specific iron uptake-related genes expression during microsclerotia development shows siderophore-mediated iron acquisition genes are rigorously upregulated speciﬁcally during the formation and mature period while reductive iron assimilation related genes just display a higher expression at the late maturation period. Abrogation of reductive iron assimilation, by the deletion of the high affinity iron permease (NrFtrA), has no visible effect on microsclerotia biogenesis in N. rileyi. In sharp contrast, N. rileyi L-ornithine-N5- monooxygenase (NrSidA), required for synthesis of all siderophores, is absolutely necessary for the development of pigmented microsclerotia. In agreement with the lower intracellular iron contents of microsclerotia in △NrSidA strains, not only the pigments, but both the number and the biomass are also noticeably reduced. Certain concentration of ROS is required for promoting microsclerotia biogenesis. Combined with expression pattern analysis of related genes and quantitative of intracellular iron or extracellular siderophore in WT and mutants, these data demonstrate the lack of adequate intracellular iron caused by the loss of the siderophore results in the deficiency of ROS detoxication. Furthermore, △NrSidA strains show significantly increased sensitivity to hydrogen peroxide. Besides, NrSidA, but not NrFtrA, play a crucial role in vegetative growth under iron-limiting conditions, conidiation and dimorphic switching. Remarkably, the slower growth of the △NrSidA strains in vivo due to a reduced capacity for iron acquisition leads to the loss of virulence in Spodoptera litura while the △NrFtrA mutants behaved as WT during infection. Together, these results prove siderophore-assisted iron mobilization is the major pathway of cellular iron uptake and essential for conidiation, dimorphism transition, oxidative stress resistance, pigmented microsclerotium formation and full virulence.